Future Roles and Opportunities for the U.S. Geological Survey - National Research Council (The National Academies Press, 2001)
The U.S. Geological Survey (USGS) has adapted to the changing political, economic, and technical state of the nation and the world since it was established in the late nineteenth century. Over a period of more than 120 years, the USGS has evolved from a small group of scientists who collected data and provided guidance on how to parcel, manage, and use the public lands of the West to an agency comprised of thousands of scientists who conduct research and assessment activities on complex scientific issues at scales ranging from the local to the global. The USGS will no doubt continue to evolve and adapt to meet changing national needs. In fact, the recent integration of the National Biological Service and parts of the U.S. Bureau of Mines into the USGS presents an ideal opportunity to examine the agency's vision, mission, role, and scientific opportunities as the organization begins the early years of the twenty-first century. The USGS recognized the need to adapt to changing demands when it asked the National Research Council (NRC) to undertake this study. The NRC formed a multidisciplinary committee of 16 experts to address issues related to the future roles, challenges, and opportunities of the agency.

Striking a Balance: Improving Stewardship of Marine Areas (The National Academies Press, 1997)
America's ocean and coastal regions2014which provide wildlife habitat, commercial fish stocks, mineral reserves, travelways, recreation, and more2014are under increasing pressure as more and more people exploit marine resources, leaving environmental damage in their wake. Striking a Balance responds to the urgency for sound decision-making in the management of marine resources. An expert committee proposes principles, goals, and a framework for marine area governance, including new governance structures at the federal and regional levels and improvements for existing governing and regulatory systems. Recommendations include using tools2014such as zoning and liability2014for resolving conflicts between users, controlling access to marine resources, and enforcing regulations. The book describes the wide-ranging nature and value of marine resources, evaluates their current management, and explores three in-depth case studies. It also touches on the implications of newer, more flexible, less hierarchical approaches to organizational behavior. Striking a Balance will be of interest to everyone concerned about marine resource management, especially federal and state marine managers and regulators, marine scientists and policy analysts, companies and organizations with interests in marine and coastal resources, and advocacy groups.

Wildland Fires: Toward Improved Understanding and Forecasting of Air Quality Impacts: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Wildland fires pose a growing threat to air quality and human health. Fire is a natural part of many landscapes, but the extent of area burned and the severity of fires have been increasing, concurrent with human movement into previously uninhabited fire-prone areas and forest management practices that have increased fuel loads. These changes heighten the risk of exposure to fire itself and emissions (smoke), which can travel thousands of miles and affect millions of people, creating local, regional, and national air quality and health concerns. To address this growing threat, the National Academies brought together atmospheric chemistry and health research communities, natural resource managers, and decision makers to discuss current knowledge and needs surrounding how wildland fire emissions affect air quality and human health. Participants also explored opportunities to better bridge these communities to advance science and improve the production and exchange of information. This publication summarizes the workshop discussions and themes that emerged throughout the meeting.

Biologic Markers of Air-Pollution Stress and Damage in Forests - National Research Council (The National Academies Press, 1989)
There is not much question that plants are sensitive to air pollution, nor is there doubt that air pollution is affecting forests and agriculture worldwide. In this book, specific criteria and evaluated approaches to diagnose the effects of air pollution on trees and forests are examined.

Snow Avalanche Hazards and Mitigation in the United States - National Research Council (The National Academies Press, 1990)
The present mortality as a result of snow avalanches exceeds the average mortality caused by earthquakes as well as all other forms of slope failure combined. Snow avalanches can range from small amounts of loose snow moving rapidly down a slope to slab avalanches, in which large chunks of snow break off and destroy everything in their path. Although considered a hazard in the United States since the westward expansion in the nineteenth century, in modern times snow avalanches are an increasing concern in recreational mountainous areas. However, programs for snow avalanche hazard mitigation in other countries are far ahead of those in the United States. The book identifies several steps that should be taken by the United States in order to establish guidelines for research, technology transfer, and avalanche legislation and zoning.

The Economic Consequences of a Catastrophic Earthquake: Proceedings of a Forum - National Research Council (The National Academies Press, 1992)
This book presents the proceedings of an August 1990 forum held at the National Academy of Sciences in Washington, D.C. Topics covered include the current and potential roles of the private sector and the various levels of government before, during, and after an earthquake occurs, and alternative strategies that could be implemented to reduce the economic impacts, with emphasis placed on the role of the insurance industry.

Soil and Water Quality: An Agenda for Agriculture - National Research Council (The National Academies Press, 1993)
How can the United States meet demands for agricultural production while solving the broader range of environmental problems attributed to farming practices? National policymakers who try to answer this question confront difficult trade-offs. This book offers four specific strategies that can serve as the basis for a national policy to protect soil and water quality while maintaining U.S. agricultural productivity and competitiveness. Timely and comprehensive, the volume has important implications for the Clean Air Act and the 1995 farm bill. Advocating a systems approach, the committee recommends specific farm practices and new approaches to prevention of soil degradation and water pollution for environmental agencies. The volume details methods of evaluating soil management systems and offers a wealth of information on improved management of nitrogen, phosphorus, manure, pesticides, sediments, salt, and trace elements. Landscape analysis of nonpoint source pollution is also detailed. Drawing together research findings, survey results, and case examples, the volume will be of interest to federal, state, and local policymakers; state and local environmental and agricultural officials and other environmental and agricultural specialists; scientists involved in soil and water issues; researchers; and agricultural producers.

Land Use and Wildlife Resources (The National Academies Press, 1970)

Solid-Earth Sciences and Society - National Research Council (The National Academies Press, 1993)
As environmental problems move upward on the public agenda, our knowledge of the earth's systems and how to sustain the habitability of our world becomes more critical. This volume reports on the state of earth science and outlines a research agenda, with priorities keyed to the real-world challenges facing human society. The product of four years of development with input from more than 200 earth-science specialists, the volume offers a wealth of historical background and current information on: Plate tectonics, volcanism, and other heat-generated earth processes. Evolution of our global environment and of life itself, as revealed in the fossil record. Human exploitation of water, fossil fuels, and minerals. Interaction between human populations and the earth's surface, discussing the role we play in earth's systems and the dangers we face from natural hazards such as earthquakes and landslides. This volume offers a comprehensive look at how earth science is currently practiced and what should be done to train professionals and adequately equip them to find the answers necessary to manage more effectively the earth's systems. This well-organized and practical book will be of immediate interest to solid-earth scientists, researchers, and college and high school faculty, as well as policymakers in the environmental arena.

Water Conservation, Reuse, and Recycling: Proceedings of an Iranian-American Workshop - National Research Council (The National Academies Press, 2005)
In December 2002, a group of specialists on water resources from the United States and Iran met in Tunis, Tunisia, for an interacademy workshop on water resources management, conservation, and recycling. This was the fourth interacademy workshop on a variety of topics held in 2002, the first year of such workshops. Tunis was selected as the location for the workshop because the Tunisian experience in addressing water conservation issues was of interest to the participants from both the United States and Iran. This report includes the agenda for the workshop, all of the papers that were presented, and the list of site visits.

Clean Coastal Waters: Understanding and Reducing the Effects of Nutrient Pollution - National Research Council
Environmental problems in coastal ecosystems can sometimes be attributed to excess nutrients flowing from upstream watersheds into estuarine settings. This nutrient over-enrichment can result in toxic algal blooms, shellfish poisoning, coral reef destruction, and other harmful outcomes. All U.S. coasts show signs of nutrient over-enrichment, and scientists predict worsening problems in the years ahead. Clean Coastal Waters explains technical aspects of nutrient over-enrichment and proposes both immediate local action by coastal managers and a longer-term national strategy incorporating policy design, classification of affected sites, law and regulation, coordination, and communication. Highlighting the Gulf of Mexico's \

Freshwater Ecosystems: Revitalizing Educational Programs in Limnology - National Research Council
To fulfill its commitment to clean water, the United States depends on limnology, a multidisciplinary science that seeks to understand the behavior of freshwater bodies by integrating aspects of all basic sciences2014from chemistry and fluid mechanics to botany, ichthyology, and microbiology. Now, prominent limnologists are concerned about this important field, citing the lack of adequate educational programs and other issues. Freshwater Ecosystems responds with recommendations for strengthening the field and ensuring the readiness of the next generation of practitioners. Highlighted with case studies, this book explores limnology's place in the university structure and the need for curriculum reform, with concrete suggestions for curricula and field research at the undergraduate, graduate, and postdoctoral levels. The volume examines the wide-ranging career opportunities for limnologists and recommends strategies for integrating limnology more fully into water resource decision management. Freshwater Ecosystems tells the story of limnology and its most prominent practitioners and examines the current strengths and weaknesses of the field. The committee discusses how limnology can contribute to appropriate policies for industrial waste, wetlands destruction, the release of greenhouse gases, extensive damming of rivers, the zebra mussel and other \

Informing an Effective Response to Climate Change - National Research Council (The National Academies Press, 2010)
Global climate change is one of America's most significant long-term policy challenges. Human activity2014especially the use of fossil fuels, industrial processes, livestock production, waste disposal, and land use change2014is affecting global average temperatures, snow and ice cover, sea-level, ocean acidity, growing seasons and precipitation patterns, ecosystems, and human health. Climate-related decisions are being carried out by almost every agency of the federal government, as well as many state and local government leaders and agencies, businesses and individual citizens. Decision makers must contend with the availability and quality of information, the efficacy of proposed solutions, the unanticipated consequences resulting from decisions, the challenge of implementing chosen actions, and must consider how to sustain the action over time and respond to new information. Informing an Effective Response to Climate Change, a volume in the America's Climate Choices series, describes and assesses different activities, products, strategies, and tools for informing decision makers about climate change and helping them plan and execute effective, integrated responses. It discusses who is making decisions (on the local, state, and national levels), who should be providing information to make decisions, and how that information should be provided. It covers all levels of decision making, including international, state, and individual decision making. While most existing research has focused on the physical aspect of climate change, Informing an Effective Response to Climate Change employs theory and case study to describe the efforts undertaken so far, and to guide the development of future decision-making resources. Informing an Effective Response to Climate Change offers much-needed guidance to those creating public policy and assists in implementing that policy. The information presented in this book will be invaluable to the research community, especially social scientists studying climate change; practitioners of decision-making assistance, including advocacy organizations, non-profits, and government agencies; and college-level teachers and students.

Facilitating Climate Change Responses: A Report of Two Workshops on Knowledge from the Social and Behavioral Sciences - National Research Council (The National Academies Press, 2010)
The William and Flora Hewlett Foundation, understanding the need for policy makers at the national level to entrain the behavioral and social sciences in addressing the challenges of global climate change, called on the National Research Council to organize two workshops to showcase some of the decision-relevant contributions that these sciences have already made and can advance with future efforts. The workshops focused on two broad areas: (1) mitigation (behavioral elements of a strategy to reduce the net future human influence on climate) and (2) adaptation (behavioral and social determinants of societal capacity to minimize the damage from climate changes that are not avoided). Facilitating Climate Change Responses documents the information presented in the workshop presentations and discussions. This material illustrates some of the ways the behavioral and social sciences can contribute to the new era of climate research.

Integrating Social and Behavioral Sciences Within the Weather Enterprise - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Our ability to observe and forecast severe weather events has improved markedly over the past few decades. Forecasts of snow and ice storms, hurricanes and storm surge, extreme heat, and other severe weather events are made with greater accuracy, geographic specificity, and lead time to allow people and communities to take appropriate protective measures. Yet hazardous weather continues to cause loss of life and result in other preventable social costs. There is growing recognition that a host of social and behavioral factors affect how we prepare for, observe, predict, respond to, and are impacted by weather hazards. For example, an individual's response to a severe weather event may depend on their understanding of the forecast, prior experience with severe weather, concerns about their other family members or property, their capacity to take the recommended protective actions, and numerous other factors. Indeed, it is these factors that can determine whether or not a potential hazard becomes an actual disaster. Thus, it is essential to bring to bear expertise in the social and behavioral sciences (SBS)2014including disciplines such as anthropology, communication, demography, economics, geography, political science, psychology, and sociology2014to understand how people's knowledge, experiences, perceptions, and attitudes shape their responses to weather risks and to understand how human cognitive and social dynamics affect the forecast process itself. Integrating Social and Behavioral Sciences Within the Weather Enterprise explores and provides guidance on the challenges of integrating social and behavioral sciences within the weather enterprise. It assesses current SBS activities, describes the potential value of improved integration of SBS and barriers that impede this integration, develops a research agenda, and identifies infrastructural and institutional arrangements for successfully pursuing SBS-weather research and the transfer of relevant findings to operational settings.

Predicting Invasions of Nonindigenous Plants and Plant Pests - National Research Council (The National Academies Press, 2002)
Nonindigenous plants and plant pests that find their way to the United States and become invasive can often cause problems. They cost more than 100 billion per year in crop and timber losses plus the expense of herbicides and pesticides. And this figure does not include the costs of invasions in less intensively managed ecosystems such as wetlands. Nonindigenous Plants and Plant Pests examines this growing problem and offers recommendations for enhancing the science base in this field, improving our detection of potential invaders, and refining our ability to predict their impact. The book analyzes the factors that shape an invader's progress through four stages: arriving through one of many possible ports of entry, reaching a threshold of survival, thriving through proliferation and geographic spread, and ultimate impact on the organism's new environment. The book also reviews approaches to predicting whether a species will become an invader as well as the more complex challenge of predicting and measuring its impact on the environment, a process involving value judgments and risk assessment. This detailed analysis will be of interest to policymakers, plant scientists, agricultural producers, environmentalists, and public agencies concerned with invasive plant and plant pest species.

Safety is Seguridad: A Workshop Summary - National Research Council (The National Academies Press, 2003)
Approximately 32.8 million persons of Hispanic descent live in the United States, half of whom were born outside the United States (Therrien and Ramirez, 2000). By the year 2050, it is expected that Hispanics will constitute more than 25 percent of the total U.S. population and approximately 15 percent of the U.S. labor force. These estimates and the fact that 90 percent of Hispanic American men and 60 percent of Hispanic American women participate in the U.S. workforce strongly suggest a need for occupational safety and health information in Spanish. The growing presence of Spanish-speaking workers and employers in the United States and the unprecedented 12-percent increase in the overall rate of workplace fatalities among Hispanic workers in 2000 highlights the need to better communicate occupational safety and health information in Spanish to both employees and employers. To address this need the National Institute for Occupational Safety and Health (NIOSH) is preparing a strategy for developing and disseminating Spanish-language occupational safety and health educational and technical material. To gather information necessary to create this strategic plan the National Research Council (NRC) was asked to host a workshop. The committee commissioned five white papers (see Appendices D-H) and organized a workshop on May 29-30, in San Diego, California. Safety is Seguridad: A Workshop Summary is a synopsis of the presentations and discussions at the workshop. It does not contain any conclusions and recommendations. The conclusions and recommendations in the white papers represent the views of the authors and not necessarily those of the committee or the NRC. It is intended as input to the NIOSH strategic planning in this area. Chapter 2 discusses the available information and identifies information gaps regarding risks and adverse events for Latino workers. Chapter 3 examines the available health and safety training resource materials for Latino workers, especially for those with little or no English capabilities; in particular, it discusses issues of the linguistic and cultural appropriateness of materials. Chapter 4 considers issues surrounding the assessment of existing materials and the development of new materials. Chapter 5 discusses the various means of conveying information to Spanish-speaking workers, again focusing on cultural appropriateness and ways of maximizing understanding. Chapter 6 summarizes the discussion in the prior chapters and presents some overarching issues raised by the workshop attendees.

America's Climate Choices - National Research Council
Climate change is occurring. It is very likely caused by the emission of greenhouse gases from human activities, and poses significant risks for a range of human and natural systems. And these emissions continue to increase, which will result in further change and greater risks. America's Climate Choices makes the case that the environmental, economic, and humanitarian risks posed by climate change indicate a pressing need for substantial action now to limit the magnitude of climate change and to prepare for adapting to its impacts. Although there is some uncertainty about future risk, acting now will reduce the risks posed by climate change and the pressure to make larger, more rapid, and potentially more expensive reductions later. Most actions taken to reduce vulnerability to climate change impacts are common sense investments that will offer protection against natural climate variations and extreme events. In addition, crucial investment decisions made now about equipment and infrastructure can \

Observing Weather and Climate from the Ground Up: A Nationwide Network of Networks - National Research Council
Detailed weather observations on local and regional levels are essential to a range of needs from forecasting tornadoes to making decisions that affect energy security, public health and safety, transportation, agriculture and all of our economic interests. As technological capabilities have become increasingly affordable, businesses, state and local governments, and individual weather enthusiasts have set up observing systems throughout the United States. However, because there is no national network tying many of these systems together, data collection methods are inconsistent and public accessibility is limited. This book identifies short-term and long-term goals for federal government sponsors and other public and private partners in establishing a coordinated nationwide \

Mountains of Madness: A Scientist's Odyssey in Antarctica - John Long
This extraordinary book is the first-person account of John Long's two unforgettable \